STORYTELLING DALAM PERSPEKTIF NARATIVE PARADIGMA : SEBUAH KAJIAN TEORITIS - Yunus Winoto; Prijana Prijana (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2017)
The low interest and reading habits of Indonesian children have become an issue which attracted the attention of many parties. Various attempts have been made, either through the provision of facilities and infrastructures as well as various activities that encourage the reading interest of the children. We realize that the interest and reading habits of children will not grow by itself. Rather, they need to be nurtured and developed. One effort to foster the interest is through storytelling activities. Through this activity, children are expected to be interested in reading books or reading materials whose stories have been presented in storytelling activities. In scientific activities, the topics of storytelling activities are often used as research materials. One theory which is often used as a theoretical framework is the narrative paradigm by Walter R Fisher. The basic assumption in the narrative paradigm explains that humans are essentially storytellers (homo narran). The application of Narrative Paradigm in research focusing on storytelling is considered fixed because it is able to explain elements in storytelling, such as the storyteller and elements of the story.